PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE DI INDONESIA - Khoiriyah, Ma'rifatul; Dewi, Nurma Gupita (Universitas Sarjanawiyata Tamansiswa, 2024)
This research attempts to prove the influence of company size, capital structure and investment decisions on company value in food and beverage entities on Indonesia Stock Exchange 2019-2021. This research uses the dependent variable of company value, while the independent variables are company size, capital structure and investment decisions. The population is 33 food and beverage entity on the 2019-2021 BEI. The documentation approach is employed by the data collecting methodology. Purposive sampling was used to select the sample. There were 16 entities in the research sample, totaling 48 observations. Multiple linear analysis approaches were employed as the data analysis method. To determine the Best Linear Unbias Estimate (BLUE) data, the data was evaluated using the traditional assumption test prior to the regression. Considering the outcomes of the hypothesis test, it shows that company size and capital structure have an insignificant negative effect on company value, while investment decisions have an insignificant positive effect on company value.